The speed and strength training of middle distance runners from a functional point of view - Gonschinska, I. (New Studies in Athletics, 1996)
Beitrag des Trainers I.G. (u.a. Nico Motchebon) auf dem 2. Internationalen Trainersymposium Lauf des DLV, Berlin 1996.